PENINGKATAN PRODUCTIVE SKILLS BAHASA INGGRIS PADA SISWA SEKOLAH DASAR MELALUI FUN-LEARNING - Evi Puspitasari (Universitas Muhammadiyah Yogyakarta, 2018)
This program aimed to create a wide space for students to practice productive skills of English inSpeak First Bilingual School, Klaten. Steps to run this program are planning, implementation, andevaluation to investigate learning outcomes of the program. Planning covered need analyisis,coordination with the school stake holders such as teachers and the headmaster, and programdesigning. Then in implementation, the approach employed was Fun-learning and the method wasPPP (Presentation, Practice, and Production). The approach and the method were clearly mirroredthrough the activities such as puzzle arranging, storytelling, singing a song, and making card toexpress apology. Since the moment when the program ran was in Ramadhan month, all activitieswere under the same theme, Prophet Jonah and the Whale. Last, in the evaluation process, it couldbe known that the outcome of the program was enabling students to practice English productivelyand comprehend the story of Prophet Jonah and the Whale. All of them were able to reveal theirfeeling if they were Prophet Jonah when he was thrown away to the sea in an oral form and theywere also able to make a card to express their apology in English.